Study of Emotional Intelligence Facing by Undergraduate Students Due to Environmental Situation - Kauser Fatima, Syeda; Kauser Fatima, Syeda; Qasmi, Faiza (International Journal of Psychosocial Rehabilitation, 2025)
Education for each and every individual plays a prominent role in the development of a country. In the present scenario how the hereditary is adding from a father to the child in the same way the skills of employment need to be exchanged from the ipresent generation to the upcoming generation. Our main objective in our present paper is discussion of environmental factors affecting a under graduate student such as infrastructure, parental occupation and now a day’s education is at its high cost (means how a student ichanging his goal due to lack of appropriate funds to continue his goal). These are the main factors affecting a student emotionally which must be addressed to save our upcoming generation.